Analysis of the genomic sequences and metabolites of Serratia surfactantfaciens sp. nov. YD25T that simultaneously produces prodigiosin and serrawettin W2. (December 2016) - Su, Chun; Xiang, Zhaoju; Liu, Yibo; Zhao, Xinqing; Sun, Yan; Li, Zhi; Li, Lijun; Chang, Fan; Chen, Tianjun; Wen, Xinrong; Zhou, Yidan; Zhao, Furong
Abstract Background Gram-negative bacteria of the genusSerratia are potential producers of many useful secondary metabolites, such as prodigiosin and serrawettins, which have potential applications in environmental bioremediation or in the pharmaceutical industry. SeveralSerratia strains produce prodigiosin and serrawettin W1 as the main bioactive compounds, and the biosynthetic pathways are co-regulated by quorum sensing (QS). In contrast, theSerratia strain, which can simultaneously produce prodigiosin and serrawettin W2, has not been reported. This study focused on analyzing the genomic sequence ofSerratia sp. strain YD25T isolated from rhizosphere soil under continuously planted burley tobacco collected from Yongding, Fujian province, China, which is unique in producing both prodigiosin and serrawettin W2. Results A hybrid polyketide synthases (PKS)-non-ribosomal peptide synthetases (NRPS) gene cluster putatively involved in biosynthesis of antimicrobial serrawettin W2 was identified in the genome of YD25T, and its biosynthesis pathway was proposed. We found potent antimicrobial activity of serrawettin W2 purified from YD25T against various pathogenic bacteria and fungi as well as antitumor activity against Hela cells. Subsequently, comparative genomic analyses were performed among a total of 133Serratia species. The prodigiosin biosynthesis gene cluster in YD25T belongs to the type Ipig cluster, which is the main form ofpig -encoding genes existing in most of the pigmentedSerratia species. In addition, a complete autoinducer-2 (AI-2) system (includinglux S, lsr BACDEF, lsr GK, andlsr R) as a conserved bacterial operator is found in the genome ofSerratia sp. strain YD25T . Phylogenetic analysis based on concatenated Lsr and LuxS proteins revealed that YD25T formed an independent branch and was clearly distant from the strains that solely produce either prodigiosin or serrawettin W2. The Fe (III) ion reduction assay confirmed that strain YD25T could produce an AI-2 signal molecule. Phylogenetic analysis using the genomic sequence of YD25T combined with phylogenetic and phenotypic analyses support this strain as a member of a novel and previously uncharacterizedSerratia species. Conclusion Genomic sequence and metabolite analysis ofSerratia surfactantfaciens YD25T indicate that this strain can be further explored for the production of useful metabolites. Unveiling the genomic sequence ofS. surfactantfaciens YD25T benefits the usage of this unique strain as a model system for studying the biosynthesis regulation of both prodigiosin and serrawettin W2 by the QS system.